2022
DOI: 10.1364/oe.466036
|View full text |Cite
|
Sign up to set email alerts
|

Transmissive coding metasurface with dual-circularly polarized multi-beam

Abstract: The Pancharatnam-Berry (PB) phase can be used to control the phase of circularly polarized electromagnetic waves. However, there are few studies on the modulation of dual-circularly polarized multi-beam using the transmissive coding metasurface. A scheme of spin-controlling multi-beam by transmissive coding metasurface is proposed for dual-circular polarization simultaneously. The transmissive coding metasurface (TCMS) can transmit linearly polarized incidence into multi-beam with orthogonally circular polariz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 61 publications
(20 citation statements)
references
References 37 publications
0
15
0
Order By: Relevance
“…Interestingly, the co-pol component of the beam at 30 • is whereas it is RHCP at −30 • . This can be attributed to the Pancharatnam-Berry (PB) phase of the reflector as the condition of π/2 phase difference between v− and u− polarized phases imposed by ( 1) is a geometric phase to its 1-bit phase gradient [14].…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, the co-pol component of the beam at 30 • is whereas it is RHCP at −30 • . This can be attributed to the Pancharatnam-Berry (PB) phase of the reflector as the condition of π/2 phase difference between v− and u− polarized phases imposed by ( 1) is a geometric phase to its 1-bit phase gradient [14].…”
Section: Resultsmentioning
confidence: 99%
“…It also has significant advantages of low profile, low cost, and ease of fabrication. [17][18][19][20][21] Therefore, metasurfaces can provide a new way to generate OAM beam. Recently, to easily realize OAM in microwave frequency, metasurfaces have been demonstrated by a series of experiments.…”
Section: Doi: 101002/adts202200842mentioning
confidence: 99%
“…Again, due to inherently band limited nature of these resonances, a working multi-band design that can operate over many microwave bands remains a huge design challenge. Recent studies have demonstrated the design and validation of coding metasurfaces for the conversion of linear to circular multi-beam radiation [21,22]. In this article we present a simple, single-layer metasurface design that achieves cross-conversion for horizontally or vertically polarized incident wave in the reflection mode.…”
Section: Introductionmentioning
confidence: 99%